Uncertainty shocks, monetary policy and long-term interest rates - Gianni Amisano; Oreste Tristani (European Central Bank (ECB), 2019)
We study the relationship between monetary policy and long-term rates in a structural, general equilibrium model estimated on both macro and yields data from the United States. Regime shifts in the conditional variance of productivity shocks, or "uncertainty shocks", are an important model ingredient. First, they account for countercyclical movements in risk premia. Second, they induce changes in the demand for precautionary saving, which affects expected future real rates. Through changes in both risk-premia and expected future real rates, uncertainty shocks account for about 1/2 of the variance of long-term nominal yields over long horizons. The remaining driver of long-term yields are changes in inflation expectations induced by conventional, autoregressive shocks. Long-term inflation expectations implied by our model are in line with those based on survey data over the 1980s and 1990s, but less strongly anchored in the 2000s.
Keywords: C11; C34; E40; E43; E52; 330; monetary policy rules; uncertainty shocks; term structure of interest rates; regime switches; Bayesian estimation